Evaluasi Kebijakan Penyelenggaraan Telekomunikasi dan Informatika di Kabupaten Merauke - Syukron, Nurkholis (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
Communication as a social process that is lived by humans is one of the important components for every individual to maintain their existence in the midst of an increasingly dynamic social life. The Merauke Regency Government regulates and manages the activities of its constituents in terms of communication in the Merauke Regency Regional Regulation Number 5 of 2019 concerning the Implementation of Communication and Informatics. This study aims to determine how the value generated from the implementation of communication policies in Merauke Regency, Papua. This study uses William N. Dunn's public policy evaluation analysis knife with five indicators namely, effectiveness, adequacy, equity, responsiveness and accuracy. This research is a descriptive research with a qualitative approach. The use of qualitative descriptive methods is carried out in order to comprehensively reveal and understand various phenomena that occur in order to obtain a clearer picture of the aspect being studied. Based on the results of the study, it can be seen that the telecommunications and informatics policies implemented by the Merauke Regency Government are categorized as still not effective, not yet able to meet the adequacy of meeting public needs, not being evenly distributed in a positive way, less responsive and not well implemented. This happened because the implementation of policies on telecommunications and informatics as one of the basic needs of modern society was held in order to simply fulfill the obligations of the Merauke Regency Government. Keywords: Evaluation, Public Policy, Telecommunications and Informatics.